Financing Infrastructure in the 21st Century - Dexter Whitfield (Don Dunstan Foundation, Australian Institute f, 2006)
The Private Finance Initiative/Public Private Partnership (PPP/PFI) debate is locked into technical issues about financing, on/off balance sheet accountancy, risk allocation, efficiency, narrow value for money matters and the procurement process. This report draws together the recent experience, trends and developments of PPP/PFIs and Strategic Service-delivery Partnerships (SSPs) in Britain and the development of PPPs in Australia. The objective is to generate a wider debate on the longer-term issues of accountability, sustainability, the future of public services, the role of government and the provision of the social and economic infrastructure. The early PPP/PFI projects were usually major transport infrastructure schemes in the late 1980s and early 1990s. However, PPP/PFI was soon extended to other types of infrastructure such as schools, hospitals, prisons and courts. A number of ambitious ICT projects were developed in the mid 1990s but after a series of long delays, cost overruns and service failures, ICT projects were excluded from the PPP/PFI programme. The introduction of the National Health Service (NHS) Local Improvement Finance Trusts (LIFT) and Building Schools for the Future (BSF) models further embed private finance and private provision within the public sector. None of the reforms of PPP/PFI such as reducing the scope of facilities management contracts, seconding rather than transferring staff, making the procurement process more participative, increasing community benefits obtained in the procurement process and limiting the scope and powers of Special Purpose Vehicles (SPVs) or Joint Venture Companies (JVCs) have little bearing on the critique of PPP/PFI and the analysis of its long-term impact. Radical reform of risk transfer and value for money criteria would mean that most PPP/PFI projects never proceed beyond the options appraisal stage. A four-part typology of privatisation and marketisation provides a framework to explain and understand the different ways in which public services and the welfare state are being transformed. The different forms of marketisation are part of a broader restructuring of the state in the interests of capital. In Britain, 750 PPP/PFI deals have been signed with a total capital value of A$130 billion (£48.4 billion) up to March 2006 (see Table 4). A further 200 projects requiring A$65 billion (£26 billion) capital investment are expected to be signed in the next five years. By 2010/11, the total capital value of PPP/PFI projects is forecast to be A$195 billion (£75 billion). In addition, 22 Strategic Service-delivery Projects, centred on ICT and the transformation of corporate services (valued at over A$8billion (£3bn) and employing 10,000 staff) have been established in Britain since 2000 with a further four in procurement. However, two SSP projects have been terminated and a third substantially reduced. Nearly forty-five PPP projects have been signed in Australia with a further 18 projects in procurement according to the National PPP Forum database. There are some important differences between PPP/PFI projects in Britain and Australia. In Britain, the scale and scope of projects are larger and there is a much wider range of projects with a more extensive role in the welfare state and social infrastructure. There is also much stronger employment legislation to protect jobs, terms and conditions compared to further deregulation of employment in Australia. New PPP/PFI models in health and education provide opportunities to include core services in PPP/PFI projects in Britain. New markets have emerged in Britain for refinancing of project debt and PPP/PFI equity disposals (contractors wanting to realise profits and recycle capital into new projects). In order to assess the extent to which the longer term impact of PPP/PFI has been considered in policy and research reports, a sample of 25 studies were examined from Global/European, British and Australian sources. They are divided into three groups - government policy and evaluation reports, consultants and business reports, and academic/policy studies.